Magnitude and Measurement Module Through Learning Cycle 7E: Innovation Based on Local Potential of Sago Plants for Critical Thinking - Marlina, Marlina; Karim, Karim; Suyidno, Suyidno (SEJ (Science Education Journal), 2025)
Critical thinking skills are essential for solving problems in everyday life. However, these skills are still lacking in physics learning at school. Therefore, this study analyzes the feasibility of the magnitude and measurement module with the learning cycle 7E based on the local potential of sago plants to improve students’ critical thinking skills. This research is a development research with a 4D model. The subjects of the limited trial were 10 students, and the field trial was 16 students from one of the MAN's in Barito Kuala Regency, South Kalimantan. The research data were obtained through module validation sheets, critical thinking tests, and learner response questionnaires. The results showed that the content and construct validation of modules and essential thinking tests were highly valid. In addition, students’ responses in terms of ease of use of the module, the attractiveness, and the benefits of the module in physics learning in the practical category. It is concluded that the module of magnitude and measurement with learning cycle 7E, based on the local potential of sago plants developed, is feasible to improve students’ critical thinking skills.